2016
DOI: 10.1016/j.celrep.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

HIV Triggers a cGAS-Dependent, Vpu- and Vpr-Regulated Type I Interferon Response in CD4 + T Cells

Abstract: Several pattern-recognition receptors sense HIV-1 replication products and induce type I interferon (IFN-I) production under specific experimental conditions. However, it is thought that viral sensing and IFN induction are virtually absent in the main target cells of HIV-1 in vivo. Here, we show that activated CD4 T cells sense HIV-1 infection through the cytosolic DNA sensor cGAS and mount a bioactive IFN-I response. Efficient induction of IFN-I by HIV-1 infection requires proviral integration and is regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 58 publications
9
91
1
Order By: Relevance
“…It is important to mention that cGAS can also be implicated in sensing RNA viruses [12]. In an intriguing study, Vermeire et al reported that activated CD4 + T cells sense HIV-1 infection through cGAS, originally described as a DNA sensor, and promote a type I IFN response, although it remains unknown how [49]. Mankan et al showed that cGAS can bind RNA:DNA hybrid to form cGAMP, with subsequent activation of STING [50].…”
Section: Dissecting Sting Signalingmentioning
confidence: 99%
“…It is important to mention that cGAS can also be implicated in sensing RNA viruses [12]. In an intriguing study, Vermeire et al reported that activated CD4 + T cells sense HIV-1 infection through cGAS, originally described as a DNA sensor, and promote a type I IFN response, although it remains unknown how [49]. Mankan et al showed that cGAS can bind RNA:DNA hybrid to form cGAMP, with subsequent activation of STING [50].…”
Section: Dissecting Sting Signalingmentioning
confidence: 99%
“…However this response is dependent on endocytosis, and thus is not a byproduct of productive infection. The specific relevance of cGAS-STING signaling in sensing of HIV-1 infection in infected pDCs is still unclear, although human pDCs harbor a functional cGAS-STING pathway [86].…”
Section: Innate Immune Response To Hiv-1 Infection In Dcs and Macrophmentioning
confidence: 99%
“…It is reported that Vpr may have a positive effect on IFN-I induction during HIV-1 infection of monocytes-derived DC (MDDCs) or monocytes-derived macrophages (MDMs) (Zahoor et al, 2015;Zahoor et al, 2014). In contrast, others have reported a suppressive role of Vpr on IFN-I production in MDDCs and MDMs (Harman et al, 2011;Mashiba et al, 2014), or in cell lines, such as HEK293, HeLa and HeLa-derived STING-expressing reporter cells (Vermeire et al, 2016).…”
Section: Ifn-i Induces a Number Of Anti-viral Factors To Inhibit Hiv-mentioning
confidence: 99%